Cover Feature: Aluminum(III) Salen Complexes as Active Photoredox Catalysts (Eur. J. Org. Chem. 10/2020). Issue 10 (19th December 2019) - Gualandi, Andrea; Marchini, Marianna; Mengozzi, Luca; Kidanu, Hagos Tesfay; Franc, Antoine; Ceroni, Paola; Cozzi, Pier Giorgio
Abstract : The Cover Feature shows the "salen's curse"! As described in the present paper, it is possible to consider aluminum complexes as active photocatalysts. In particular, commercially available ClAl(Salen) metal complex showed a remarkable reactivity in a benchmark photocatalytic alkylation of aldehydes. The possibility to tailor photophysical properties of Salen ligand and to apply the framework towards stereochemical control are opening new perspectives for photoredox mediated transformations. More information can be found in the Full Paper by A. Gualandi, P. Ceroni, P. G. Cozzi et al.